2022
DOI: 10.4049/jimmunol.2200042
|View full text |Cite
|
Sign up to set email alerts
|

Dicer and PKR as Novel Regulators of Embryonic Stem Cell Fate and Antiviral Innate Immunity

Abstract: Embryonic stem cells (ESCs) represent a unique cell population in the blastocyst stage embryo. They have been intensively studied as a promising cell source for regenerative medicine. Recent studies have revealed that both human and mouse ESCs are deficient in expressing IFNs and have attenuated inflammatory responses. Apparently, the ability to express IFNs and respond to certain inflammatory cytokines is not “innate” to ESCs but rather is developmentally acquired by somatic cells during differentiation. Accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 119 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…Unlike differentiated cells, ESCs exhibit a much weaker response to cytoplasmic double-stranded RNA (dsRNA) and produce minimal amounts of IFN-β 93 . This reduced innate immune response might serve as a protective mechanism, allowing ESCs to avoid immune-related cytotoxicity 92 . Our results suggest that the inability to silence ERVs and repetitive elements activates an "innate immune checkpoint", leading to the elimination of cells that cannot suppress these elements during naïve-to-primed transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike differentiated cells, ESCs exhibit a much weaker response to cytoplasmic double-stranded RNA (dsRNA) and produce minimal amounts of IFN-β 93 . This reduced innate immune response might serve as a protective mechanism, allowing ESCs to avoid immune-related cytotoxicity 92 . Our results suggest that the inability to silence ERVs and repetitive elements activates an "innate immune checkpoint", leading to the elimination of cells that cannot suppress these elements during naïve-to-primed transition.…”
Section: Discussionmentioning
confidence: 99%
“…ESCs are immunologically different from somatic cells 92 . Unlike differentiated cells, ESCs exhibit a much weaker response to cytoplasmic double-stranded RNA (dsRNA) and produce minimal amounts of IFN-β 93 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, using this in vitro dicing assay, they found that aviD is more resistant to LGP2 [40]. Whether other cofactors of Dicer, such as PKR‐associated activator (PACT), protein kinase RNA‐activated (PKR) and adenosine deaminases acting on RNA 1 (ADAR1), modulate the Dicer's ability to cleave dsRNA in vivo needs to be further investigated [68–70].…”
Section: Other Than Truncated Dicer Full‐length Dicer Can Also Proces...mentioning
confidence: 99%